Peran Earnings Management Memediasi Ukuran Wajah Maskulinitas CEO Pria terhadap Performance - Bustanul Ulum; Rusdiyanto Rusdiyanto; Suyanto Suyanto (Fakultas Ekonomi dan Bisnis, 2023)
This study investigates how earnings management affects how masculine a CEO's attitude toward performance is. Structural Equation Modeling using Software Stata is used in the study to examine data from Indonesian Stock Exchange businesses for the years 2018 through 2022. The results indicate that earnings management, with increases and decreases in earnings management having an impact on the size of the CEO's face, mediates the relationship between a male CEO's masculinity and performance. The results can aid in the development of Financial Accounting Standard No. 19 by the Indonesian Accountants Association and show that earnings management mediates the size of a CEO's manly face toward performance